Arşiv Belgelerine Göre Selahaddin Eyyûbî'nin Kudüs Vakıfları / According to Archive Sources Salahaddin Ayyubi's Foundations in Jerusalem - Sağlam, Nevzat (Journal of History Culture and Art Research, 2017)
Abstract Jerusalem was remained under the dominion of the Latin kings for eighty-eight years untill conquered by Salahaddin Ayyubi. Salahaddin Ayyubi, who started an intensive work for reconstruction of the city following the conquest, has pioneered many services in areas of education, health, religion and culture with his foundation works. Although Salahaddin Ayyubi’s work on charitable foundations in Jerusalem is included in previous studies conducted on the history of Jerusalem, but no independent work specific to this issue has been done. In this article, archival documents that have not been published before were evaluated and the issues related to the foundations established by Salahaddin Ayyubi in Jerusalem and the administration of these foundations, especially in the recent periods of the Ottoman Empire, have been highlighted. Besides, the negative effects of negative developments in Jerusalem in the form of building and construction of temples on Salahaddin Eyyubi foundations has also been pointed out. Öz Kudüs seksen sekiz yıl Latin Krallığı'nın hâkimiyetinde kaldıktan sonra Selahaddin Eyyûbî tarafından fethedilmiştir. Fethi müteakip şehrin yeniden imarı için yoğun bir çalışma başlatan Selahaddin Eyyûbî, kurduğu vakıf eserleriyle eğitim, sağlık, din ve kültür alanlarında birçok hizmete öncülük etmiştir. Kudüs tarihine dair yazılmış olan eserlerde Selahaddin Eyyubî'nin Kudüs'teki vakıflarına ilişkin bilgilere yer verilmekle beraber tespit edebildiğimiz kadarıyla müstakil bir çalışmanın konusu yapılmamıştır. Bu makalede daha önce yayınlanmamış arşiv belgeleri de değerlendirilerek Selahaddin Eyyubî'nin Kudüs'te tesis ettiği vakıflar ve özellikle Osmanlı'nın son dönemlerinde bu vakıfların idaresine ilişkin hususlar ele alınmıştır. Ayrıca Kudüs'te gayr-i müslimlerin mülk edinme ve mabet inşa etme çabalarının vakıflar aleyhine doğurduğu olumsuz gelişmelerden Selahaddin Eyyubî vakıflarının nasıl etkilendiğine de bu çalışmada yer verilmiştir.